ANALISIS PENDAPATAN DAN STRATEGI PENGEMBANGAN PADI DI KABUPATEN DELI SERDANG - Siti Sara; Satia Negara Lubis; Sarim Sembiring (JURNAL PROINTEGRITA, 2019)
The purpose of this study was to identify and compare the income and costs of IR64 and Ciherang rice farming in Deli Serdang District and The Rice Development strategy in Deli Serdang Regency.The methode of the research is the survey methode that is direct observation like interviews and questionnaires to the sample farmers. The sample of this study amounted to 60 people. Divided into 2 subdistricts. The amount uses the formulation of determining purposive sampling. The analysis used is I = TR-TC. To show whether there are significant differences between the IR64 varieties and Ciherang used the t test. By using the confidence level of 0.01 (99%) and 0.05 (95%). The results of the study show that rice farming in Deli Serdang District based on financial analysis still get the benefits for both Ciherang and IR 64 varieties with the results of the R / C 1.8 ratio. Based on the results of the t test, the income of IR 64 variety is higher than the Ciherang variety. Development strategies with improved technology and innovation by utilizing opportunities the strengths include expanding planting areas, increasing productivity effectively and also involving the government in providing site-specific that is targeted for development.